2015
DOI: 10.1002/jeab.183
|View full text |Cite
|
Sign up to set email alerts
|

Intraverbal naming and equivalence class formation in children

Abstract: Six typically developing children between 5 and 7 years of age underwent match-to-sample training to establish three-member equivalence classes after first acquiring a unique name for each stimulus. Horne and Lowe's (1996) naming hypothesis predicts that under those circumstances, match-to-sample training contingencies may establish intraverbal relations between the unique names, which in turn guide correct responses on a subsequent test for stimulus equivalence. Following training of baseline relations (AB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
1
14
1
3
Order By: Relevance
“…In conclusion, this study adds support to the previous research suggesting that equivalence‐class performances may be either influenced (e.g., Carp & Petursdottir, ) or established by participants' verbal behavior (e.g., Ma et al, ). Future research should attempt to replicate our results using four‐ to five‐member classes of arbitrary stimuli across participants with varying verbal skills.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In conclusion, this study adds support to the previous research suggesting that equivalence‐class performances may be either influenced (e.g., Carp & Petursdottir, ) or established by participants' verbal behavior (e.g., Ma et al, ). Future research should attempt to replicate our results using four‐ to five‐member classes of arbitrary stimuli across participants with varying verbal skills.…”
Section: Discussionsupporting
confidence: 86%
“…The authors measured response latencies from the onset of the sample and selection of the comparison, and found that the longest latencies occurred during baseline trials, which were presented first. These results contradict previous findings that suggest that longer latencies are more likely to be observed during transitivity and equivalence trials (e.g., Carp & Petursdottir, ). However, with one‐node relations (i.e., three‐member classes), significant differences in response latencies are typically not observed (Bentall, Jones, & Dickins, ).…”
contrasting
confidence: 88%
See 1 more Smart Citation
“…The low performance on generalized responding exhibited by Gabriel can be attributed to deterioration of the original 2D equivalence relations, but for Sabrina, even with the 2D equivalence relations intact, and the ability to perform quasi‐identity matching, there was no equivalence generalization. Although well observed in the literature, variability in equivalence class formation in preschool children has been discussed only recently (Carp & Petursdottir, ; Petursdottir, Carp, Peterson, & Lepper, ; Pilgrim, Click, & Galizio, ). Thus, it is unsurprising that a more complex phenomenon (i.e., generalization of emergent relations) could also show variability.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, there are reports of equivalence emerging without naming (Carr, Wilkinson, Blackman, & McIlvane, 2000;Lazar, Davis-Lang, & Sanchez, 1984;Luciano, Gómez-Becerra, & Rodríguez-Valverde, 2007;O'Donnell & Saunders, 2003;Sidman & Tailby, 1982). And on the other hand, some authors have questioned those results, claiming that naming is necessary for equivalence to emerge (Carp & Petursdottir, 2015;Horne, Hughes, & Lowe, 2006;Horne, Lowe, & Randle, 2004;Lowe, Horne, Harris, & Randle, 2002).…”
Section: Introductionmentioning
confidence: 99%